2007
DOI: 10.2151/jmsj.85b.363
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Urban Meteorology :A Review

Abstract: This paper reviews the progress made in urban meteorology over the past few decades. The focus is on the impact of urban surfaces on the overlying atmosphere along the conventional meteorological frameworks. Section 1 details the difficulties in generalizing urban surfaces in a meteorological sense because of surface diversity, and considers whether conventional similarity law is applicable. Section 2 describes the characteristics of urban surfaces as the bottom boundary of the atmosphere and includes a discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 213 publications
(228 reference statements)
1
63
0
2
Order By: Relevance
“…Ashworth, 1929) and an increased activity during the 50's and 60's of the 20th century (e.g. see review in Lawrence, 1971;Kanda, 2007) was observed. These previous studies focused on the impact of human activities near the major sources of heat and air pollution emissions, which are mainly concentrated in urban, semi-urban and industrial areas.…”
Section: A Sanchez-lorenzo Et Al: Assessing Large-scale Weekly Cyclmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashworth, 1929) and an increased activity during the 50's and 60's of the 20th century (e.g. see review in Lawrence, 1971;Kanda, 2007) was observed. These previous studies focused on the impact of human activities near the major sources of heat and air pollution emissions, which are mainly concentrated in urban, semi-urban and industrial areas.…”
Section: A Sanchez-lorenzo Et Al: Assessing Large-scale Weekly Cyclmentioning
confidence: 99%
“…4.2.2). This paper will focus on a review of studies about "large-scale" WCs (for a review of urban WC's see Arnfield, 2003 andKanda, 2007), which is a more recent topic in scientific literature, thus holding major uncertainties and some confusion. Also, to our knowledge, a review of this subject is still lacking.…”
Section: A Sanchez-lorenzo Et Al: Assessing Large-scale Weekly Cyclmentioning
confidence: 99%
“…While this ensured that all sites observed emissions from similarly sized source areas, each instrument was likely located at a different vertical position within its respective boundary layer. For example, observations from urban Boston and Worcester were likely affected by building topography and the corresponding changes in micrometeorology and atmospheric mixing [60,61]. Methodological challenges (e.g., urban tall tower construction) in elevating instruments above the roughness layer combined with differences in boundary layer height at each location prevented similar instrument positioning within each plume/boundary layer.…”
Section: Instrumentation and Data Analysismentioning
confidence: 99%
“…The computational fluid dynamics (CFD) technique in its many forms provides a wide range of technical options for investigation [9]. While RANS based models still have a role to play, the use of LES modelling can explicitly resolve atmospheric flows of various scales ranging from an individual roughness element to an entire boundary layer [10]. Various urban flow and dispersion models have been developed based on CFD to simulate the complicated wind pattern and pollutant transport [9].…”
Section: Introductionmentioning
confidence: 99%